COMMUNITY DEVELOPMENT DENGAN INSTRUMEN ZAKAT PROFESI DI DESA JUMOYO, KECAMATAN SALAM, KABUPATEN MAGELANG - Mochlasin Mochlasin (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
The purpose of this study was to determine how the implementation of community development programs using profession zakat that was proclaimed by Jumoyo Lor community, Jumoyo Village, District Salam, Magelang. This research includes field research based on case studies; the research was conducted intensive, detailed and in-depth to an organization, institution or certain symptoms. Data was categorized then interpreted by a model interpretation surface structure and deep structure. Results of this study indicate that there has been a community development activity by relying on their own potential, by exploring the potential of zakat profession. At least the basic needs such as rice, shelter, health and education have been attempted to be fulfilled by the communities themselves, although in a minimal level